Unraveling the gut microbiota’s role in PCOS: a new frontier in metabolic health - Li, Caihong; Cheng, Dongkai; Ren, Haiqin; Zhang, Tao (Frontiers in Endocrinology, 2025)
Polycystic ovary syndrome (PCOS) is a common endocrine and metabolic disorder affecting reproductive-age women, characterized primarily by hyperandrogenism, ovulatory dysfunction, and metabolic abnormalities. In recent years, the gut microbiota has garnered widespread attention for its potential role as a key regulator of host metabolism in the pathogenesis of PCOS. Studies have shown that PCOS patients exhibit dysbiosis in their gut microbiota, characterized by reduced microbial diversity, an imbalance in the ratio of Firmicutes to Bacteroidetes, changes in the abundance of specific taxa, and abnormal levels of metabolic products. These alterations may exacerbate metabolic dysfunction in PCOS through multiple mechanisms, including influencing host energy metabolism, disrupting lipid and bile acid metabolism, and inducing chronic inflammation. Addressing gut dysbiosis through the modulation of patients’ microbiomes—such the use of, prebiotics, fecal microbiota transplantation, and optimizing diet lifestyle—may offer strategies for improving metabolic abnormalities and alleviating clinical symptoms in PCOS. Additionally, the gut microbiome promises as a potential marker, aiding in the precise diagnosis and personalization of PCOS. Although our current understanding of how the gut microbiota influences PCOS is still limited, research is needed to explore the causal relationships and mechanisms involved, providing a more reliable theoretical basis for clinical. This review aims summarize the research progress on the relationship between gut microbiota and PCOS, and to suggest future directions to promote the development of prevention and treatment strategies for PCOS.